ASPEK BIOLOGI REPRODUKSI IKAN LEMEDUK (Barbodes schwanenfeldii) DI SUNGAI BELUMAI KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA - Siti Aisyah; Darma Bakti; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
The purpose of this research is to know the reproduction (the sex ratio, the gonad maturity level, the gonad maturity index, the size of the first mature gonad, fecundity, and the egg diameter). This research was done in May until June 2014 in four different locations by using census method. The sex ratio is consisting of 21 females fishes and 34 male fishes with a balanced sex ratio. The maturity gonad level for lemeduk female and male are found in I–IV. The gonad maturity index for female is 0,05% – 9,66% and for male is 0,05% – 9,75%. The size of the first mature gonad for male fish is 193 mm. The fecundity of female lemeduk is 5.345–54.372 eggs. The distribution of the female lemeduk egg diameter is 0,068–0,1202 mm.Keyword : Belumai River, Fish reproduction, Barbodes schwanenfeldii.,